Technical high education links between the regional development and students: case study of the Instituto Nor Oriental de la Selva in the San Martin region - Yalta Gonzales, Ruth (2023)
This research seeks to know how, from a case of a public institute in the San Martín region, Peru, it contributes to its region based on its links with the productive structure and with its students. For this, interviews were carried out with key actors in the educational environment of the institute, such as students and management personnel. Likewise, a documentary analysis of the main national and regional plans, policies and evaluations was carried out. This allowed us to know the perceptions and subjectivities of these linked actors, all based on their own experience, such as family and educational background.